The Physical And Microbiological Quality Of Clean Water In Nanas Sub Village Kediri District Post Natural Phenomena Sinking Wells - Clairine Maretha Martin Putra (Universitas Airlangga, 2018)
Indonesia prones to natural disasters because it is located at the meeting of three world's major tectonic plates that move and collide each other. The natural phenomena of sinking well that occurs in 2017 damaging 79 wells in the Nanas sub village, Puncu sub-district, Kediri district. The sinking well is natural phenomena which causes wells to down or to sink underground. The highest percentage of sinking well is in Nanas sub-village, There are 40 (50.6%) of wells are damaged. The research purpose was to know the physical quality and microbiology of well water in Nanas sub-village. This research type was observational. Samples were taken by purposive sampling. The water samples were obtained from 10 wells which were not damaged, 10 wells which were once muddy, and 10 wells which were sunk in 2017. The water check results were compared to regulation of the Minister of Health no. 32 in 2017 about Environmental Health Quality Standards and Water Requirements for Hygiene Sanitation, Swimming Pool, SPA and Public Bath. This research result was 30 (100%) water source fulfilled the physical quality requirement, and 28 (93,3%) qualified microbiology quality, while the remaining 2 (6,7%) did not fulfill the microbiological quality requirements for the need of hygiene and sanitation. The physical and microbiological quality of well water, after the natural phenomena of sinking wells, is qualified. The society is expected to maintain clean water sources.